Lebanos : ochi eton imperialismo kai ton sionismo (Hellenic Committee for International Solidarity)
Map of Lebanon shaped as an arm with a blood transfusion inserted into it Original title: Λίβανος : οχι ετον ιμπεριαλισμο και τον σιωνιεμο PO-1331